ICT diffusion in Hungary Nyuga-Dunántúl region - Péter Tóth (Netcom)
The acceptance of info communication technologies (ICT) is an inevitable element of rural development since the infrastructure is more or less developed in Hungary. The problem of acceptance lies in the attitude toward new technologies. In this paper we would like to describe the process where the use of a certain service available only in an online environment becomes popular among the rural population. Using the best known Hungarian social network site IWIW registrants data on settlements and users of a Hungarian NUTS II region combined with spatial and demographic statistics one could describe the scale and direction of diffusion processes which adds some more information to the facts we already know on state of information society in Hungary.